KUALITAS PELAYANAN SURAT PENGANTAR NIKAH BERBASIS APLIKASI PALUI DI KELURAHAN SUNGAI ANDAI KECAMATAN BANJARMASIN UTARA KOTA BANJARMASIN - Rahmat Fazar; Erma Ariyani (Universitas Lambung Mangkurat, 2019)
The purpose of this research was to measure the Quality of Marriage-Based Services for Marriage Coverages Based on the Palui Application in Sungai Andai Village, Banjarmasin Society still considers services related to making Marriage Certificate is very slow due to the lack of public awareness of digital world insights. In this study the authors used a qualitative method, to get the information done through the interview. Collection of field facts notes using the method of observation-documentation, and analysis of data. The main focus in this paper is the quality of service delivery procedures for marriage attendants measured and analyzed with a qualitative descriptive approach and using 5 service quality indicators according to Zeithaml, namely: Tangibles, Reliability, Responsiveness, Assurance and Emphathy. The results showed that the quality of public services in Sungai Andai Banjarmasin Village has run quite well even though there are still residents who are not satisfied with the quality of service. Based on the processing of marriage registration services based on the Palui Applications in Sungai Andai Banjarmasin, measured by 5 indicators of service quality, there are factors influencing the quality of service of marriage attendant records covering 3 supporting factors, namely (1) work experience as supporting expertise (2) work motivation for employees enthusiasm and diligence, and (3) awareness of serving the community so as to educate well. While the inhibiting factors, namely (1) the problem of the speed of internet access Palui which makes the process slow (2) lack of public awareness of insight in the digital age (3) lack of information for the community, and (4) lack of socialization regarding a marriage certificate.